Circulating Receptor-Interacting Protein Kinase 3 Are Increased in HBV Patients With Acute-on-Chronic Liver Failure and Are Associated With Clinical Outcome - Chen, Liwen; Cao, Zhujun; Yan, Lei; Ding, Yezhou; Shen, Xinghua; Liu, Kehui; Xiang, Xiaogang; Xie, Qing; Zhu, Chuanwu; Bao, Shisan; Wang, Hui (Frontiers in Physiology, 2020)
Backgrounds and aims: Necroptosis is a newly identified type of cell death with programmed pathways. The current study was to investigate necroptosis by measuring its key regulators, receptor interacting protein kinase 3 (RIPK3) and mixed lineage kinase domain-like (MLKL) in patients with HBV related acute-on-chronic liver failure. Methods: HBV-ACLF patients (n=90), non-ACLF patients without cirrhosis (N=70) and with cirrhosis (N=40) and healthy controls (HC) (n=70) were enrolled for the study. All the patients were subject to serum RIPK3 measurement. Hepatic RIPK3 and MLKL were also determined in the livers from 18 patients and 5 donors, using immunohistochemistry. Results: Serum RIPK3 was significantly elevated in HBV-ACLF patients compared to that of non ACLF patients and HC. Serum RIPK3 in ACLF patients at the recruitment was significantly higher in non-survivors than those in survivors at 90-day follow-up. The predictive accuracy of serum RIPK3 at 90-day outcome was relative good with an area under the receiver operating curve (AUROC) of 0.72 (p<0.001), similar to that of the MELD score (0.76, p<0.001). The combined use of RIPK3 and MELD score further increased the AUROC to 0.80. The hepatic RIPK3 and MLKL measured by immunohistochemistry, significantly increased in the patients with HBV-ACLF than the patients without ACLF and HC. Conclusion: Circulating RIPK3 was significantly increased in patients with HBV-ACLF and was associated with clinical outcome. The improved combined objective scores could offer additional prognostic value in ACLF patients for physicians with more accurate expectations.